ANALISIS IMPLEMENTASI MANAJEMEN PERUBAHAN TERHADAP KEPEMIMPINAN DAN BUDAYA KERJA SERTA PENGARUHNYA PADA KINERJA KARYAWAN DI BANK JATIM CABANG BANYUWANGI - Achmad Budi Yusthisia (STIE Mandala Jember, 2017)
This research was conducted at Bank Jatim Branch of Banyuwangi. samples used in this study as many as 100 samples from a population of 150 people by sampling using simple random sampling. The purpose of this study was to examine the effect of the change management leadership and work culture and its influence on employee performance. Data analysis techniques in this study using Structural Equation Modeling (SEM). The results showed that there is significant influence between management changes to leadership, there is significant influence between management changes to workplace culture, there is significant influence between management changes to employee performance, there is significant influence between the leadership of the working culture, there is significant influence among the leadership on employee performance and there is no significant influence between the work culture on employee performance.